Continent-wide effects of urbanization on bird and mammal genetic diversity. Issue 1920 (12th February 2020) - Schmidt, C.; Domaratzki, M.; Kinnunen, R. P.; Bowman, J.; Garroway, C. J.
Abstract : Urbanization and associated environmental changes are causing global declines in vertebrate populations. In general, population declines of the magnitudes now detected should lead to reduced effective population sizes for animals living in proximity to humans and disturbed lands. This is a cause for concern because effective population sizes set the rate of genetic diversity loss due to genetic drift, the rate of increase in inbreeding and the efficiency with which selection can act on beneficial alleles. We predicted that the effects of urbanization should decrease effective population size and genetic diversity, and increase population-level genetic differentiation. To test for such patterns, we repurposed and reanalysed publicly archived genetic datasets for North American birds and mammals. After filtering, we had usable raw genotype data from 85 studies and 41 023 individuals, sampled from 1008 locations spanning 41 mammal and 25 bird species. We used census-based urban–rural designations, human population density and the Human Footprint Index as measures of urbanization and habitat disturbance. As predicted, mammals sampled in more disturbed environments had lower effective population sizes and genetic diversity, and were more genetically differentiated from those in more natural environments. There were no consistent relationships detectable for birds. This suggests that, in general, mammal populations living near humans may have less capacity to respond adaptively to further environmental changes, and be more likely to suffer from effects of inbreeding.